The impact of Prophylactic cranial irradiation on the prognosis of patients with limited-stage small cell lung cancer in the MRI era - Mengyuan Chen; Zehua Sun; Jingcong Pan; Yujin Xu; Yuezhen Wang; Ming Chen; Xiao Hu (Radiation Oncology)
Abstract Purposes To evaluate the impact of prophylactic cranial irradiation (PCI) on the prognosis of patients with limited-stage small cell lung cancer (SCLC) in the era of MRI surveillance. Methods Limited-stage SCLC patients with complete remission (CR) or partial remission (PR) of tumor after definitive chemo-radiotherapy (CRT) were retrospectively analyzed. Survival data were calculated by Kaplan-Meier methods, Cox proportional hazards model was applied for multivariate prognostic analysis. Results Between June 2002 and January 2017, 620 patients with limited-stage SCLC were accrued in our study. After CRT, 228 (36.8%) patients achieved CR, of whom, 29 patients did not receive PCI, among the rest 199 patients, 172 (86.4%) received brain MRI to exclude brain metastasis (BM) before PCI. With a median follow-up time of 25.6 months, the cumulative BM rate was 17.1% and 37.9% in patients who received or did not receive PCI (P = 0.011). The median survival time was 30.2 months and 30.5 months, respectively and the 1 -, 3 -, 5-year survival rates were 93.7%, 42.9%, 35.8% and 83.4%, 46.5%, 41.9%, respectively (P = 0.98). Multivariate analysis indicated that baseline KPS ≥ 90 was a favorable independent prognostic factor for OS in CR patients (HR: 0.33, 95% CI: 0.23–0.46, P = 0.000). After CRT, 392 (63.2%) patients achieved PR, 53 cases did not receive PCI and 310 (91.4%) of the remaining 339 patients received brain MRI before PCI. With a median follow-up time of 15.5 months, the cumulative brain metastasis rate was 12.7% and 46.2% respectively (P = 0.000). The median survival time was 25.7 months and 18.6 months, respectively. The 1 -, 3 -, and 5-year survival rates were 87.6%, 40.2%, 29.2% and 75.7%, 16.7%, 10.3% (P = 0.000). Baseline KPS ≥ 90 (HR: 0.32, 95% CI: 0.25–0.41, P = 0.000) and PCI (HR: 0.57, 95% CI: 0.41–0.79, P = 0.001) were favorable prognostic factors for OS in PR patients. Conclusions In this study, PCI significantly reduced the incidence of BM in patients with limited-stage SCLC who were evaluated as CR and PR after CRT, but it has no significantly positive impact on overall survival in CR patients. Further prospective randomized studies were warranted.